2021
DOI: 10.33448/rsd-v10i4.13682
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade financeira de sistemas agroflorestais biodiversos no Centro Oeste Brasileiro

Abstract: Os sistemas agroflorestais biodiversos (SAF’s) combinam espécies arbóreas frutíferas ou lenhosas, com culturas agrícolas e/ou criação de animais, em uma mesma área. Para o agricultor que o detém, esses sistemas trazem melhoria da qualidade de vida econômica, social e ambiental, pois proporcionam formas sustentáveis de produção de alimentos, segurança alimentar, além da preservação ambiental. O estudo apresenta a análise de viabilidade financeira de dois modelos de sistemas agroflorestais implantados no municíp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
3
0
14
Order By: Relevance
“…Oliveira et al (2008), when evaluating the fi nancial viability of a 4-year-old silvopastoral system with Eucalyptus grandis planted in triple rows with a spacing of 3.0 x 1.5 m between trees and 34 m in rows (density of 500 individuals per hectare), with an interest rate of 6% per year and a horizon of 21 years, found an NPV of 7,239.06 R$/ha, proving to be viable from this analysis criterion. Garcia et al (2021) analyzed biodiverse agroforestry systems that refl ect the reality of family farming over a period of 20 years, and found that both SAF's 1 and 2, with NPV values of R$ 11,018.24 and 40,377.04 respectively, presented conditions of fi nancial viability. The same authors highlighted that SAF 2 was slightly more profi table compared to the other, since its BCR was 1.2, diff erent from SAF 1, which was 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2008), when evaluating the fi nancial viability of a 4-year-old silvopastoral system with Eucalyptus grandis planted in triple rows with a spacing of 3.0 x 1.5 m between trees and 34 m in rows (density of 500 individuals per hectare), with an interest rate of 6% per year and a horizon of 21 years, found an NPV of 7,239.06 R$/ha, proving to be viable from this analysis criterion. Garcia et al (2021) analyzed biodiverse agroforestry systems that refl ect the reality of family farming over a period of 20 years, and found that both SAF's 1 and 2, with NPV values of R$ 11,018.24 and 40,377.04 respectively, presented conditions of fi nancial viability. The same authors highlighted that SAF 2 was slightly more profi table compared to the other, since its BCR was 1.2, diff erent from SAF 1, which was 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Para compor os arranjos de sistemas agroflorestais propostos, realizou-se um estudo multidisciplinar, seguindo preceitos adotados por Martinelli et al (2019), Mayer (2019), Garcia et al (2021) e Padovan et al (2022). Iniciou-se com pesquisa de campo realizada no período de 2016 a 2020, ocasião em que foram visitadas trinta propriedades rurais de agricultores familiares que possuem sistemas agroflorestais situados nos estados de Mato Grosso do Sul, Paraná e São Paulo.…”
Section: Metodologiaunclassified
“…Para as indicações de espécies arbóreas nativas destinadas ao ecótono entre Mata Atlântica e Cerrado, bem como ao bioma Cerrado, também considerou-se o Código Florestal Brasileiro (Brasil, 2012), informações e recomendações de Costa et al (2010), Ávila et al (2011), Martins e Cavararo (2012), Ferreira et al (2013), Campos Filho e Sartorelli (2015), Zavala et al (2017), Padovan et al (2018a, b), Mayer (2019), Fernandes et al (2020), Nascimento et al (2020, Padovan et al (2021Padovan et al ( , 2022 e Ribeiro et al (2022).…”
Section: Metodologiaunclassified
See 2 more Smart Citations